Hydrographic analysis of Iluh River (Batman) in relation to flood and torrent events - Sunkar, Murat; Tonbul, Saadettin (Elsevier Science Bv, 2011)
Iluh River, which flows through Batman city, Turkey, overflows almost every year and gives damage to its surrounding environment. The side branches that are linked to Iluh River in the city center cause flood events. The flood and torrent events experienced in the autumn of 2006 due to Iluh River and its branches caused 10 deaths and material damage of about 15 million Euros. Besides human factors, the hydrographic characteristics of Iluh River are also effective on the occurrence of such catastrophic flood and torrent events. The analyzing of these characteristics and determination of their effect on the occurrence of flood and torrent events are of utmost importance for Batman city. The basin of Iluh River, which has a pyramidal shape and seasonal flow, covers an area of 316 km(2). In this study, morphometric and hydrographic analyses were made on digital maps in order to reveal the hydrographic characteristics of the basin. GPS measurements were performed with granolumetry and infiltration experiments in field surveys. The results of the analyses reveal that the slope is low, the stream intensity is high, the soil is clayey, and the infiltration capacity is low in the basin of Iluh River. Furthermore, it was shown that the rivers in the city had shifted outside their natural streambeds and the canal constructed on Iluh River was designed according to the basin area and maximum flow rate. Such factors and the basin are among the hydrographic characteristics which give rise to flood and torrent events of great intensity and frequency in the city. (C) 2011 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The 2nd International Geography Symposium-Mediterranean Environment
2nd International Geography Symposium-Mediterranean Environment -- JUN 02-05, 2010 -- Antalya, TURKEY
Keywords: Batman city; Iluh River; flood and torrent; hydrographic characteristics